Stress and Cardiovascular Disease - Hjemdahl, Paul; Rosengren, Annika; Steptoe, Andrew (Springer London : Imprint: Springer, 2012)
There is a growing trend for the incorporation of stress management into cardiac rehabilitation programs and into preventive cardiology. However, stress is multifaceted, often misunderstood, and requires as much scientific scrutiny as other pathological processes relevant to cardiology. The quality of research into stress management is variable, and care is required in identifying effective evidence-based methods. There is thus a need for better understanding of stress and its ramifications among cardiologists, other clinicians caring for cardiac patients, and by those involved in primary prevention. Stress and Cardiovascular Disease provides an up to date survey of research, highlighting the clinical implications of physiological and population studies of stress.  Each chapter addresses a particular aspect of this exciting field of basic and clinical research.  This multidisciplinary volume will serve as an aid to physicians in their management of stress-related issues in cardiac patients and high-risk individuals.